Phenotypic and genetic characterization of sixteen grain and dual-type industrial hemp varieties (Cannabis sativa L.) for agronomic and yield component traits - Tamang, Kusum Raj; Mawhinney, Thomas P.; Carson, Christian B.; Asiamah, Joshua Yeboah; Mahdi, Sakina Haruna; Reed, Emily; Sharma, Swastika; Koirala, Prabesh; Patel, Jaimin; Mensah, Clement Akotsen; Valliyodan, Babu (Frontiers in Plant Science, 2025)
Industrial hemp (Cannabis sativa L.) is a multipurpose crop primarily grown for fiber, grain, and cannabinoids. Due to its high-quality protein and oil composition, industrial hemp grain is increasingly an important crop for a nutritional source. Although the global demand for hemp grain is increasing, research exploring the genetic and climatic effects on agronomic and seed composition traits is limited. Furthermore, there has been very little research conducted on seed development and shattering. Therefore, to study this biological phenomenon and for optimal hemp grain production in Missouri, suitable cultivars for this production region were compared to identify the best-suited ones. Key physiological and seed compositional traits were studied. We found significant variation in plant height, diameter, biomass, grain yield, crude protein, and crude fat among the evaluated varieties. The dual type variety, Futura 83, showed superior performance and yield and has many suitable traits for the Missouri production region, with the grain yield ranging from 2434–2793 kg/ha. In addition, we studied the expression of two candidate genes associated with seed shattering resistance and flowering. Both genes were expressed differentially among various hemp tissues. The expression of the GmPdh1 homolog gene was higher in mature seeds, and the GmDt1 homolog was higher in flower tissues, suggesting their potential role in seed dispersal and flowering. However, further research is required for functional validation and increasing the crop yield and seed composition.